2006
DOI: 10.3354/meps323171
|View full text |Cite
|
Sign up to set email alerts
|

Model for growth and survival of mussels Mytilus edulis reared in Prince Edward Island, Canada

Abstract: Mathematical models of commercially important species enable one to integrate the diversity of information on these species, understand mechanisms responsible for observed population dynamics, and assess management scenarios. We present a population model for blue mussels Mytilus edulis grown in suspended culture in 2 bays in Prince Edward Island, Canada. The model incorporates a number of ecological processes, namely allometric growth of individual mussels, temperature-dependent growth rates (based on the Las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…The effective-density method was developed for the analysis of an intertidal tunicate (Guiñez and Castilla 2001). The multilayer method was applied to suspensiongrown mussels (Lachance-Bernard et al 2010) and provided estimates of the 3-D ST exponent which are consistent with the present study i.e., that ST in suspension-grown mussels is driven by spatial constraints (see also Lauzon-Guay et al 2006). This conclusion clearly diverges from that of Filgueira et al (2008), who reported FST in suspension-grown mussels using the effective-density method.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The effective-density method was developed for the analysis of an intertidal tunicate (Guiñez and Castilla 2001). The multilayer method was applied to suspensiongrown mussels (Lachance-Bernard et al 2010) and provided estimates of the 3-D ST exponent which are consistent with the present study i.e., that ST in suspension-grown mussels is driven by spatial constraints (see also Lauzon-Guay et al 2006). This conclusion clearly diverges from that of Filgueira et al (2008), who reported FST in suspension-grown mussels using the effective-density method.…”
Section: Discussionsupporting
confidence: 61%
“…They found β = [−0.557, −0.423], suggesting that ST was driven by competition for space. Lauzon-Guay et al (2006), using a population model of growth and survival of mussels cultured on long lines in two estuaries of Prince Edward Island, Canada, also concluded that mussel population density was regulated by spatial constraints. Although these studies were based on different numerical methods, all involved similar mussel species grown in suspension (Mytilus edulis, M. galloprovincialis and M. trossulus).…”
Section: Introductionmentioning
confidence: 99%
“…We used the metric of 'elasticity', in which the effect of proportional (rather than absolute) perturbations on a given output quantity are evaluated (Caswell 2001). Elasticity is defined as: (13) where S P (%) is the elasticity of the output quantity to a given % increase in parameter P, x 0 is the output of the original model and x P is the output of the model modified for parameter P (Barbeau & Caswell 1999, Lauzon-Guay et al 2006. Elasticities of B* (critical transition weight) and t* (critical transition age) to independent perturbations of d ƒ , T ƒopt , ƒ opt , p 1 , a 2 , b 2 , p 2 , d, T opt and m opt were calculated at 2 levels of parameter change, namely at 1 and 5%.…”
Section: Methodsmentioning
confidence: 99%
“…3 in AlunnoBruscia et al 2000;e.g., Figs. 5 and 7 in Fréchette et al 2000; but see Lauzon-Guay et al 2006). A further example of ambient conditions being reflected in stocking experiments is found in mussel rafts (provided that the conventional a = 0.05 significance level is used instead of a = 0.01, as used by Fuentes et al 2000).…”
Section: Introductionmentioning
confidence: 94%